Momentum Effects and Pakistan Stocks Exchange - Aftab Hussain Tabasam; Lubna Jamil; Muhammad Nadeem Khan; Aadil Farooq Khan (Journal of Management Practices, Humanities and Social Sciences, 2022)
This article employs 25 momentum techniques to analyze the momentum impacts using a sample of 466 non-financial enterprises from the Pakistan Stock Exchange for the years 2007 to 2017. CAPM and the Carthart four-factor model were also used to examine risk factors in this article. The Carthart four factor model results demonstrate a strong relationship between risk and returns due to systematic risk, and the positive and statistically highly significant coefficient of size factor (SMB) suggests that small minus big stocks are responsible for the returns of a portfolio. In contrast, the negative and very significant coefficient of factors (HML) and momentum factors (MOM) imply that the momentum and HML factor perfectly negatively explains the dependent variable and that the momentum profits are almost nonexistent. Furthermore, it is concluded that Carhart models are able to define variation in stock return for above given factors and are appropriate for Pakistan stock exchange.The results of the monthly 25 short-term momentum strategies and the 16 long-term strategies show that there is no momentum in Pakistani stock. Furthermore, this article discovered that only one-third of strategies and six out of nine create anomalous returns. These returns are caused, respectively, by systematic risk and manager performance. This analysis came to the conclusion that there are no momentum effects present in the Pakistan stock exchange, according to all momentum portfolios. According to this report, investors shouldn't use momentum tactics to make investments in Pakistan's capital market. According to this article, the sample size should be enlarged, and daily stock, bond, and commodity data should be used to review the momentum effects. Furthermore, contrarian momentums as well as early and late stage momentum strategies should apply in order to see the existence and robustness of momentum.